(untitled) (LACCEI, 2024)
Additive manufacturing (AM) is an attractive fabrication method in several industrial fields, including the construction sector, also called Architecture, engineering, and construction industry (AEC). This technique’s popularity is continuously growing due to the benefits over traditional methods, such as rapid production, custom parts, and reduced material waste, offering opportunities to develop complex shapes with geometric freedom and a high degree of detail and achieving a high degree of automation. Addressing AM from the early stages of conceptual design allows greater exploitation of its benefits. Thus, this study tackles a conceptual redesign approach to adapt traditional blocks into additively manufactured blocks. The methodology was inspired by conceptual design as defined by VDI 2221, including design thinking mindsets as a source of idea generation. A functional analysis was performed to characterize this product and obtain two redesign options: internal diamond-shaped and rectangular-shaped cells, with the possibility of integrating phase change materials. A numerical analysis performed in ANSYS© coupled with Rhinoceros© and Voxelprint© showed that the rectangular-shaped cells using AM-adapted concrete complied with ASTM C90 standardized bricks.